Listening to the Breath, Chanting the Word: The Two Breaths in María Zambrano’s Clearings of the Forest - Ferrández, Raquel (Poligrafi, 2023)
Clearings of the Forest (Claros del Bosque, 1977), one of the most poetic and challenging works of María Zambrano’s thought, cannot be approached from a breathless paradigm. For the immersion in these clearings take us into the breathing of being that we contemplate alongside the more obvious physiological breathing, the breathing of life. In this work, Zambrano proposes a poetic and mystical phenomenology of the breathing of being through the breathing of its word. Thus, to recover contact with this inner breathing could be to recover the lost chant of the word. This essay does not pretend to be a detailed analysis of Zambrano’s thought as a whole, nor of the vibrant mystery that her clearings reveal. The purpose is to uncover the fundamental role that breathing plays in this poetic-philosophical journey, along with other symbols such as light or love, with the question of what place this type of philosophical exercise occupies today in the classrooms of contemporary universities.